THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, AND LIFESTYLE ON THE FINANCIAL BEHAVIOR OF THE MILLENNIAL GENERATION - Ratna Sari; Basuki Toto Rahmanto (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study aims to analyze the effect of financial literacy, financial technology, and lifestyle on the financial behavior of the millennial generation in Jatisampurna Subdistrict, Bekasi City. The background of this research is based on the importance of millennials ability to manage finances effectively amid the development of digital financial technology and changes in consumption patterns. The population of this study consists of millennials residing in Jatisampurna Subdistrict, totaling 8,140 individuals, with a sample of 99 respondents determined using the Slovin formula with a 10% margin of error. This study employs multiple linear regression analysis. The results indicate that financial literacy and financial technology influence the financial behavior of the millennial generation in Jatisampurna Subdistrict, while lifestyle does not influence the financial behavior of the millennial generation in Jatisampurna Subdistrict.